Agama dan Penanggulangan Kemiskinan: Studi Kasus Masyarakat Pesisir di Kabupaten Takalar, Sulawesi Selatan - Abdullah (Al-Ulum, 2021)
This paper focuses on examining the role of religion in improving the work ethic of fishing communities in Takalar Regency. The approach used in this research is the Socio-theological Approach (Social monotheism). The social theological approach is a method or method used to link the sociological level of religious or divine society in order to analyze and reveal data on the reality under study. The data acquisition technique is to use data collection methods in the form of observation, interviews and documentation. The results of this study indicate that religion (Islam) plays a role in building work ethic. Poverty can make a person disbelieve in his Lord. Islam teaches its adherents to share with those who are entitled in terms of the theological concept of zakat as poverty alleviation and as a means of realizing social welfare. Islam does not close the space for its adherents to achieve economic prosperity. The framework of monotheism in Islamic teachings has outlined social involvement for its followers to always care and help others.